2017
DOI: 10.1017/jmo.2017.23
|View full text |Cite
|
Sign up to set email alerts
|

How work–family enrichment influence innovative work behavior: Role of psychological capital and supervisory support

Abstract: This paper examines the relationship between bi-directional work–family enrichment, psychological capital, and supervisor support in promoting innovative work behavior. We hypothesized that work-to-family enrichment and family-to-work enrichment would have a positive relation with psychological capital. Further, we examined that psychological capital would mediate the relationship between (i) work-to-family enrichment and innovative work behavior, and (ii) family-to-work enrichment and innovative work behavior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
86
0
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(102 citation statements)
references
References 104 publications
8
86
0
8
Order By: Relevance
“…Specifically, high supervisor support buffered the effects of job pressure on new mothers' depression in low‐income families (Perry‐Jenkins, Smith, Goldberg, & Logan, ), ameliorated the effects of daily work–family conflict on employed parents' negative affect (Almeida et al, ), and predicted better mental health among a sample of lesbian and gay new parents (Goldberg & Smith, ). Powerful supervisors limited stigma in using work–family supportive policies among professionals (Briscoe & Kellogg, ) , and in the service sector, supervisor support predicted innovative work behavior (Mishra, Bhatnagar, Gupta, & MacDermid Wadsworth, ).…”
Section: Paid Work and Familiesmentioning
confidence: 99%
“…Specifically, high supervisor support buffered the effects of job pressure on new mothers' depression in low‐income families (Perry‐Jenkins, Smith, Goldberg, & Logan, ), ameliorated the effects of daily work–family conflict on employed parents' negative affect (Almeida et al, ), and predicted better mental health among a sample of lesbian and gay new parents (Goldberg & Smith, ). Powerful supervisors limited stigma in using work–family supportive policies among professionals (Briscoe & Kellogg, ) , and in the service sector, supervisor support predicted innovative work behavior (Mishra, Bhatnagar, Gupta, & MacDermid Wadsworth, ).…”
Section: Paid Work and Familiesmentioning
confidence: 99%
“…In recent years, according to many studies, psychological capital reveals that in order to improve the overall performance and competitive advantage of enterprises, leaders can improve the innovation performance of employees by improving their psychological capital (Lee, 2019;Muldoon et al, 2019;Yoon and Kim, 2019). Mishra et al (2019) investigated the relationship of psychological capital and leadership support in promoting innovative work behavior among 398 service sector employees, and found that the leader support is directly related to the innovation behavior, and the psychological capital completely mediated between the leader support and the innovation work behavior. Slåtten et al (2019) examined the relationship between psychological capital, social capital, and job performance and found that psychological capital was directly related to innovation behavior, job involvement, and sales performance, and both structural and relational dimensions were directly related to psychological dimensions.…”
Section: Introductionmentioning
confidence: 99%
“…Selain itu organisasi memberikan kesempatan untuk mengikuti pelatihan/training pada partisipan. Penelitian yang dilakukan oleh Mishra et al (2017) mendapatkan hasil bahwa modal psikologis dapat memprediksi perilaku kerja inovatif. Hasil dalam penelitian ini juga menemukan hubungan positif antara modal psikologis dan perilaku kerja inovatif, Hal ini dapat memperlihatkan modal psikologis dapat membantu widyaiswara dalam mengatasi berbagai tantangan terkait dengan perilaku kerja inovatif.…”
Section: Uji Hipotesis Hubungan Sumber Daya Pekerjaan Dengan Perilakuunclassified
“…Modal psikologis yang dicirikan dengan hope, self-efficacy, optimism dan resilliency. Hasil penelitian Mishra et al (2017) menujukan adanya hubungan positif dan signifikan antara psychological capital dan innovative work behavior.…”
unclassified